HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KEMANDIRIAN PERSONAL HYGIENE PADA ANAK PRA SEKOLAH - Julita, Warni; Arneliwati, Arneliwati; Bayhakki, Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Preschooler are children who are at the stage of growth and development that are in the range of 3-6 years. Children can grow and develop optimally if parents understand how to behave and determine the type of parenting appropriate. Parenting style will affect the level of independence of children in all fields, one of which can be done by children is in the field of Personal Hygiene. This study aims to determine the relationship of parenting with the level of personal hygiene of pre-school children at a kindergarten in Pekanbaru. The study sample was 98 respondents. The measuring instrument used is a questionnaire. The analysis used is univariate analysis to determine the frequency distribution and bivariate using Chi-square test. The results showed that from 98 respondents there were 48 people (49%) mothers who applied democratic parenting, 27 people (27.5%) applied permissive parenting, and 23 people (23.5%) applied authoritarian parenting. Of the 98 children there are 49 people (50%) independent and 49 people (50%) are quite independent. The statistical test results obtained P value (0,000) <α (0,05), so that there was a significant relationship between of parenting and the level of independence of personal hygiene in pre-school children. Keyword: independent of personal hygiene, parenting, preschooler.